Research progress on clinical application of high resolution esophageal manometry in the treatment of achalasia through peroral endoscopic myotomy - YANG Chunyu; DONG Xiangqian (Yixue xinzhi zazhi)
Achalasia (AC) is a primary disorder of esophageal motility, for which current treatments are only able to alleviate symptoms, but cannot cure the disease. Peroral endoscopic myotomy (POEM) is the most effective endoscopic technique for the treatment of AC, and has emerged as the preferred treatment modality. The diagnosis and treatment of AC, as well as the selection of POEM surgical approaches, have long been contentious topics. Therefore, this paper summarized the clinical value of high resolution esophageal manometry (HREM) in the diagnosis of AC, the formulation of POEM surgical strategy, and the prediction and evaluation of postoperative efficacy to enhance clinicians' awareness of the importance of routinely performing HREM in the diagnosis and treatment of AC, and to enhance the therapeutic efficacy of POEM when treating AC. On this basis, the future optimization of POEM for the diagnosis and treatment of AC was projected.